Pengaruh Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Fikih Di MTs Alwashiliyah Perdagangan - Siti Nur Zana; Arifmiboy Arifmiboy; Salmi Wati; Muhiddinur Kamal (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to evaluate the influence of the Contextual Teaching and Learning (CTL) learning model on learning outcomes in the Fiqh subject at MTs Al-Washiliyah Commerce. The research background includes a mismatch between the learning models used by teachers and students' learning needs, low intelligence levels, low learning motivation, irregular study habits, lack of parental attention to children's education, and the influence of the social environment. This research uses a quantitative research design with the approach